What Do We Know About Education in Colorectal Cancer Prevention?—Survey Among 1130 Medical Students - Pietrzyk, Łukasz (J Cancer Educ, 2015)
Colorectal cancer (CRC) is a global public health problem. The degree of knowledge on CRC among medical students, future physicians, brings essential implications for their patients. Therefore, to acquire information about students’ knowledge on CRC, a questionnaire survey was conducted in Medical University of Lublin, Poland, with a representative sample of 1130 medical students (basic vs. clinical 552 vs. 578; male vs. female 442 vs. 688). The questionnaire was anonymous and designed in a four-section scheme (CRC risk factors, CRC prevention, CRC symptoms, CRC screening methods). There was a significant difference in the percentage of correct answers between basic and clinical level groups (P = 0.034). In general, clinical students had higher scores for their knowledge regarding CRC. Gender impacted the students’ CRC knowledge to a lesser degree; however, if the difference was revealed, female students were more aware about CRC issues (P = 0.045). We found several important deficits in students’ knowledge on CRC. These findings should motivate the oncology education coordinator as well as our teachers to introduce innovations in education methods and training environments to enable students to gain necessary knowledge and acquire the skills and competencies that would help them to function as physicians.